2008
DOI: 10.1128/ec.00128-08
|View full text |Cite
|
Sign up to set email alerts
|

TFIIIC Binding Sites Function as both Heterochromatin Barriers and Chromatin Insulators in Saccharomyces cerevisiae

Abstract: Chromosomal sites of RNA polymerase III (Pol III) transcription have been demonstrated to have "extratranscriptional" functions, as the assembled Pol III complex can act as chromatin boundaries or pause sites for replication forks, can alter nucleosome positioning or affect transcription of neighboring genes, and can play a role in sister chromatid cohesion. Several studies have demonstrated that assembled Pol III complexes block the propagation of heterochromatin-mediated gene repression. Here we show that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 62 publications
9
93
1
Order By: Relevance
“…A similar tRNA position effect was also reported initially for the tRNA-Thr(CGU) gene upstream of CBT1 in the native chromosomal locus (Simms et al, 2004). However, more detail subsequent analysis demonstrated that tRNA-Thr(CGU) gene in its natural context serves as an insulator between STE6, an upstream gene, and CBT1, preventing the STE6 regulatory elements from affecting CBT1 transcription (Simms et al, 2008).…”
Section: Accepted M Manuscriptsupporting
confidence: 76%
“…A similar tRNA position effect was also reported initially for the tRNA-Thr(CGU) gene upstream of CBT1 in the native chromosomal locus (Simms et al, 2004). However, more detail subsequent analysis demonstrated that tRNA-Thr(CGU) gene in its natural context serves as an insulator between STE6, an upstream gene, and CBT1, preventing the STE6 regulatory elements from affecting CBT1 transcription (Simms et al, 2008).…”
Section: Accepted M Manuscriptsupporting
confidence: 76%
“…2E). The two nucleotides (T45/C) were selected based on previous observations that point mutations at those sites cause loss of barrier function of tRNA genes in yeast (15,16,39,40). Although the median enhancerblocking activity in zebrafish of the mutated MIR insulator is slightly higher, the activity variance largely increased, and thus the insulator function of the mutated MIR sequence is no longer significantly distinct (P = 0.069, median test) from the negative control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The best-characterized boundary element is the threonine transfer RNA (tRNA) gene on the telomere-proximal side of HMR (Donze et al 1999;Donze and Kamakaka 2001). Pol III transcription factors TFIIIB and TFIIIC are required for boundary function, but transcription by Pol III is dispensable (Simms et al 2008;Valenzuela et al 2009). How the transcription factors block the spread of silent chromatin is uncertain, but it is likely related to the discontinuity in the nucleosomal template caused by missing or rapidlyexchanging histones.…”
Section: Barriers and Antisilencingmentioning
confidence: 99%